Bioinspired artificial platelets: past, present and future. (2nd January 2022) - Luc, Norman F.; Rohner, Nathan; Girish, Aditya; Didar Singh Sekhon, Ujjal; Neal, Matthew D.; Sen Gupta, Anirban
Abstract: Platelets are anucleate blood cells produced from megakaryocytes predominantly in the bone marrow and released into blood circulation at a healthy count of 150, 000–400, 00 per μL and circulation lifespan of 7–9 days. Platelets are the first responders at the site of vascular injury and bleeding, and participate in clot formation via injury site-specific primary mechanisms of adhesion, activation and aggregation to form a platelet plug, as well as secondary mechanisms of augmenting coagulation via thrombin amplification and fibrin generation. Platelets also secrete various granule contents that enhance these mechanisms for clot growth and stability. The resultant clot seals the injury site to stanch bleeding, a process termed as hemostasis. Due to this critical role, a reduction in platelet count or dysregulation in platelet function is associated with bleeding risks and hemorrhagic complications. These scenarios are often treated by prophylactic or emergency transfusion of platelets. However, platelet transfusions face significant challenges due to limited donor availability, difficult portability and storage, high bacterial contamination risks, and very short shelf life ( 5–7 days). These are currently being addressed by a robust volume of research involving reduced temperature storage and pathogen reduction processes on donor platelets to improve shelf-life and reduce contamination, as well as bioreactor-based approaches to generate donor-independent platelets from stem cells in vitro. In parallel, a complementary research field has emerged that involves the design of artificial platelets utilizing biosynthetic particle constructs that functionally emulate various hemostatic mechanisms of platelets. Here, we provide a comprehensive review of the history and the current state-of-the-art artificial platelet approaches, along with discussing the translational opportunities and challenges.